2019 Academic Annual Meeting and the Frontier Seminar on "Glial Cell Function and Disease" (Nantong, China). (July 2019) - Wang, Yu-Feng; Gao, Yong-Jing
The contribution of glial activities to the functions, diseases, and repair of the central nervous system has received increasing attention in neuroscience studies. To promote the research of glial cells and increase cooperation with peers, the 2019 Academic Annual Meeting and the Frontier Seminar on "Glial Cell Function and Disease" was held in Nantong City, Jiangsu Province, China from May 24 to 26. The meeting was organized by Drs. Yong-Jing Gao and Jia-Wei Zhou of the Chinese Society of Neuroscience Glia Branch. The conference focused on the physiological and pathological functions of astrocytes, microglia, and oligodendrocytes with 25 speakers in two plenary speeches and five sections of more than 180 participants engaged in glial cell research. In the two plenary lectures, Yutian Wang from the University of British Columbia and Xia Zhang from the University of Ottawa presented "Development of NMDAR (N-methyl-D-aspartic acid receptor)-positive allosteric modulators as novel therapeutics for brain disorders" and "Mechanisms underlying cannabinoid regulation of brain function and disease, " respectively. The five sections included microglia and disease, astrocytes and disease, glioma treatment and glial imaging, oligodendrocytes and disease, and glial–neuronal interactions and disease. This meeting allowed extensive and in-depth academic exchanges on the latest research and experimental techniques, represented the highest achievements of Chinese scholars on glial cells, and promoted the cooperation between peers in the fields of glia studies.